1 1 3 + 1 + 3 1 3 + 2 3 + 1 + 3 + 5 1 3 + 2 3 + 3 3 + …
What is the sum of the first 9 terms as described above?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
n t h t e r m = n 2 ∑ n 3
n t h t e r m = n 2 [ 2 n ( n + 1 ) ] 2
∑ n t h t e r m = ∑ 4 ( n + 1 ) 2
∑ n t h t e r m = 4 1 ( ∑ n 2 + 2 ∑ n + ∑ 1 )
⇒ 4 1 ( 6 n ( n + 1 ) ( 2 n + 1 ) + 2 n ( n + 1 ) + n )
put n = 9 9 6
Your notations are wrong. You didn't specify the sum is from what set of numbers. This solution is grossly inadequate.
This was not solution, but hint.
Log in to reply
There is an error in the 5th line.It is 2 ( 2 n ( n + 1 ) )
Problem Loading...
Note Loading...
Set Loading...
The n t h term of this sequence can be represented as 1 + 3 + 5 . . . + ( 2 n − 1 ) ∑ i = 1 n i 3 Sum of odd natural numbers is n 2 .
Let x i denote the i t h term of the given equation : ∑ x i = i = 1 ∑ n i 2 ( 2 ( i ) ( i + 1 ) ) 2 ∑ x i = i = 1 ∑ n 4 ( i + 1 ) 2 Expanding ( n + 1 ) 2 : i = 1 ∑ n x i = 4 ∑ i = 1 n i 2 + 2 × ∑ i = 1 n i + n i = 1 ∑ n x i = 4 1 ( 6 n × ( n + 1 ) × ( 2 n + 1 ) + 2 × 2 n × ( n + 1 ) + n ) To find the sum of the first 9 terms, we simply plug in 9 to get i = 1 ∑ 9 x i = 4 1 ( 2 8 5 + 9 0 + 9 ) i = 1 ∑ 9 x i = 9 6